Interconnection and coexistence of heterogeneous network:requirements, challenges, and architecture - Hongbin LUO; Shan ZHANG; Zhiyuan WANG (Dianxin kexue)
With the rapid development of the network technology and applications, many networks with different types of topologies and services have been emerging, such as Internet, satellite Internet, industrial Internet, unmanned aerial vehicle swarm network, and vehicle Internet, forming a situation in which many differentiated network systems coexist, to this end, the requirements and challenges were elaborated for heterogeneous networks to be integrated and coexist.Then CoLoR, an architecture for securely and efficiently interconnect heterogeneous networks was introduced.Based on the consistent function (i.e., information transmission) among heterogeneous network systems, CoLoR introduces multi-dimensional namespace for the universal representation.Moreover, CoLoR decouples the intra-domain routing and the inter-domain routing to ensure the evolution ability.Finally, CoLoR also constructs an efficient cross-domain communication mode and a security guarantee mechanism.